Immune-Mediated Thrombotic Thrombocytopenic Purpura Following mRNA-Based COVID-19 Vaccine BNT162b2: Case Report and Mini-Review of the Literature - Buetler, Vanessa Alexandra; Agbariah, Nada; Schild, Deborah Pia; Liechti, Fabian D.; Wieland, Anna; Andina, Nicola; Hammann, Felix; Kremer Hovinga, Johanna A. (Frontiers in Medicine, 2022)
Introduction: An increasing number of case reports have associated vaccinations against coronavirus disease 2019 (COVID-19) with immune-mediated thrombotic thrombocytopenic purpura (iTTP), a very rare but potentially life-threatening thrombotic microangiopathy, which leads to ischemic organ dysfunction. Thrombus formation in iTTP is related to a severe deficiency of the specific von Willebrand-factor-cleaving protease ADAMTS13 due to ADAMTS13 autoantibodies. Methods: We present a case of iTTP following exposure to the mRNA-based COVID-19 vaccine BNT162b2 (Comirnaty ®, Pfizer-BioNTech). In addition, we review previously reported cases in the literature and assess current evidence. Results: Apart from our case, twenty cases of iTTP occurring after COVID-19 vaccination had been published until the end of November 2021. There were 11 male and 10 female cases; their median age at diagnosis was 50 years (range 14 – 84 years). Five patients (24%) had a preexisting history of iTTP. Recombinant adenoviral vector-based vaccines were involved in 19%, mRNA-based vaccines in 81%. The median onset of symptoms after vaccination was 12 days (range 5 – 37), with 20 cases presenting within 30 days. Treatment included therapeutic plasma exchange in all patients. Additional rituximab, caplacizumab, or both these treatments were given in 47% (9/19), 26% (5/19), and 5% (1/19) of cases, respectively. One patient died, despite a prolonged clinical course in one patient, all surviving patients were in clinical remission at the end of the observational period. Conclusion: Clinical features of iTTP following COVID-19 vaccination were in line with those of pre-pandemic iTTP. When timely initiated, an excellent response to standard treatment was seen in all cases. ADAMTS13 activity should be determined pre-vaccination in patients with a history of a previous iTTP episode. None of the reported cases met the WHO criteria for assessing an adverse event following immunization (AEFI) as a consistent causal association to immunization. Further surveillance of safety data and additional case-based assessment are needed.